Determinants of Domestic Violence in Indonesia from a Gender and Sociology of Law Perspective - Abidin, Kurniati; Darna, Andi; Nuzul, Andi; A. Samad, Sri Astuti; Samad, Munawwarah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Every family desire a happy household, but sometimes conflict within the family is unavoidable, resulting in domestic violence. This article aims to examine the forms of domestic violence, the determinants of domestic violence, and highlight the history of domestic violence and the implementation of Law No. 23 of 2004 concerning the Elimination of Violence. This research uses an empirical method with a gender and sociology of law approach. Data were collected in two ways: through in-depth interviews with victims of domestic violence, academics, experts in legal sociology, Islamic law, and gender experts, and through literature searches such as journal articles, books, and legal regulations. The results of the study concluded that forms of domestic violence were caused by physical, psychological, sexual violence and domestic neglect. Determinants of domestic violence include economic factors, the perpetrator's angry character, early marriage, and as a result of the social structure that exists in a patriarchal society where male power and domination are very dominant. The government has issued a law on the elimination of domestic violence to provide a clear legal basis for handling domestic violence cases (KDRT), but the implementation of the law has not been optimal. Therefore, violence against women is caused by various interrelated factors. Effective collaboration between all stakeholders not only the government, but also communities, educators, religious leaders, and non-governmental organizations is sociologically necessary to empower women. This study also found that women should be encouraged to have access to quality education that fosters intellectual development, awareness of human rights, and economic, social, and political capacity.